Unsur-unsur geografi yang mempengaruhi perkembangan daerah wisata Parangtritis, Yogyakarta=Geographical Elements Influencing the Development of J'arangtritis Tourist Area, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT The research On Geographical Elements Influencing the Development of Parangtritis Tourist Area, Yogyakarta was carried out to study geographical elements which actually and potentially support and/or limit the development of tourism in Parangtritis area Variables related to physical elements were collected through direct and indirect observation, while the variables of social elements were gathered using questionnaire. The tourist taken as repondents were 80 domestic tourists representing their respective groups. Sampling was made with accidental technique. Respondents taken from the local people were 120 household heads. The sampling technique used was stratified random samping, so that 40 household heads were obtained for the first stratum and 80 household heads for the second stratum. The results of this study indicate that: (1) the geographical elements actually supporting tourism in Parangtritis area, (2) the geographical element potentially supporting the development of tourism, (3) physical phenomena actually and potentially limiting the tourism development include: flood over low and flat areas in rainy season, erosion and sedimentation due to wind at the sandy land in dry season, and enormous and dangerous sea r Jroi.,Fs. Based on these three results, a general conclusion can be drawn, namely that the geographical elements of Parangtritis area generally support the development of that area as a tourist area.